Implementation of Design Thinking in the Development of Mathematics Lesson Plan - Effi Juliana Br Tambun1; Hela Azzahra; Bella Triandini; Deny Solihin; Enno Triandini (Culture education and technology research (Cetera), 2025)
Education in Indonesia requires learning tools that can accommodate the diversity of learner characteristics. This research aims to explore how the implementation of Design Thinking method in developing mathematics learning design at SMAN 2 Bangkinang Kota. The research method used is a case study with a qualitative approach. This research involves five main phases of Design Thinking including Empathize, Define, Ideate, Prototype, and Evaluate. At the Empathize stage, a diagnostic assessment was conducted to understand the characteristics of the learners. Next, in the Define phase, learning objectives are formulated based on the assessment results. The Ideate phase generates various learning design ideas, which are then developed into Prototypes in the form of Learner Worksheets (LKPD) and applied in the Evaluate Phase which shows that Design Thinking-based learning activities increase learner participation, although there are still challenges in analyzing data on learning outcomes and time management. This research confirms that the Design Thinking method can be an innovative solution in designing adaptive and learner-centered learning.